The effect of altitude on cycling performance: a challenge to traditional concepts - Hahn, A. G.; Gore, C. J. (Sports Medicine, 2001)
Acute exposure to moderate altitude is likely to enhance cycling performance on flat terrain because the benefit of reduced aerodynamic drag outweighs the decrease in maximum aerobic power [maximal oxygen uptake (VO2max)]. In contrast, when the course is mountainous, cycling performance will be reduced at moderate altitude. Living and training at altitude, or living in an hypoxic environment (approximately 2500 m) but training near sea level, are popular practices among elite cyclists seeking enhanced performance at sea level. In an attempt to confirm or refute the efficacy of these practices, we reviewed studies conducted on highly-trained athletes and, where possible, on elite cyclists. To ensure relevance of the information to the conditions likely to be encountered by cyclists, we concentrated our literature survey on studies that have used 2- to 4-week exposures to moderate altitude (1500 to 3000 m). With acclimatisation there is strong evidence of decreased production or increased clearance of lactate in the muscle, moderate evidence of enhanced muscle buffering capacity (beta m) and tenuous evidence of improved mechanical efficiency (ME) of cycling. Our analysis of the relevant literature indicates that, in contrast to the existing paradigm, adaptation to natural or simulated moderate altitude does not stimulate red cell production sufficiently to increase red cell volume (RCV) and haemoglobin mass (Hb(mass)). Hypoxia does increase serum erthyropoietin levels but the next step in the erythropoietic cascade is not clearly established; there is only weak evidence of an increase in young red blood cells (reticulocytes). Moreover, the collective evidence from studies of highly-trained athletes indicates that adaptation to hypoxia is unlikely to enhance sea level VO2max. Such enhancement would be expected if RCV and Hb(mass) were elevated. The accumulated results of 5 different research groups that have used controlled study designs indicate that continuous living and training at moderate altitude does not improve sea level performance of high level athletes. However, recent studies from 3 independent laboratories have consistently shown small improvements after living in hypoxia and training near sea level. While other research groups have attributed the improved performance to increased RCV and VO2max, we cite evidence that changes at the muscle level (beta m and ME) could be the fundamental mechanism. While living at altitude but training near sea level may be optimal for enhancing the performance of competitive cyclists, much further research is required to confirm its benefit. If this benefit does exist, it probably varies between individuals and averages little more than 1%.